Teknologi sebagai Solusi untuk Meningkatkan Akses Pendidikan di Daerah Terpencil - Fismariza, Wiwi; Ofianto, Ofianto (TSAQOFAH, 2025)
Access to education in remote areas of Indonesia continues to face various structural challenges, including geographical barriers, limited infrastructure, and unequal distribution of teaching personnel. In this context, the implementation of technology emerges as a potential solution to expand access and improve the quality of education in underdeveloped regions. This article aims to examine the role of technology in enhancing educational access in remote areas, while also identifying the challenges and opportunities associated with its implementation. The study adopts a descriptive qualitative approach through a literature review method, analyzing scholarly sources related to educational technology, education policy, and development strategies in 3T regions (Tertinggal, Terdepan, and Terdekat – underdeveloped, frontier, and outermost areas). The findings indicate that technologies such as internet connectivity, digital learning platforms, educational radio and television broadcasts, the Internet of Things (IoT), and artificial intelligence have opened new pathways for learners in remote locations. However, the effectiveness of these technologies depends heavily on the readiness of digital infrastructure, levels of technological literacy, responsive affirmative policies, and stakeholder synergy. The article recommends strengthening locally based policies, improving digital literacy, fostering cross-sector collaboration, and developing contextual hybrid learning models as sustainable strategies to ensure equitable access to education.